Withdrawal Arguments and Their Applications in Iraqi Personal Status Courts - Hassan, Nadia Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
The research discusses the role of withdrawal in the personal status courts in Iraq, highlighting its significance in individuals’ lives and rights. Withdrawal is defined along with its provisions, emphasizing that it occurs only when there is an agreement on a specific legal share for the heirs in the inheritance in exchange for relinquishing a part of it. The study emphasizes the importance of withdrawal in inheritance, where heirs can request to withdraw from the legal share in exchange for financial compensation. It mentions the issuance of a special document called "Withdrawal Argument" as an official legal and religious document. The research’s significance lies in the interconnection of personal status and inheritance issues with Islamic law. It addresses legal issues such as the possibility of issuing a withdrawal argument after the heir’s death, canceling the argument after agreement, and whether a non-heir can request withdrawal. The research methodology involves analyzing Iraqi legal texts alongside relevant judicial decisions on withdrawal arguments. It covers topics like defining withdrawal, its conditions, forms, as well as the process of submitting a withdrawal request, obtaining a withdrawal argument, and the competent court.